2020
DOI: 10.3892/or.2020.7490
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of MMP‑1 inhibits the progression of colorectal cancer by suppressing the PI3K/Akt/c‑myc signaling pathway and EMT

Abstract: The present study aimed to investigate the role of matrix metalloproteinase-1 (MMP-1) in the development of colorectal cancer and reveal the mechanism underlying this progression. Bioinformatics methods and a public dataset were first used to analyze MMP-1 gene expression in a public dataset. MMP-1 expression in colorectal cancer patients was assessed by immunohistochemistry; its association with clinicopathological parameters and its significance for prognosis were analyzed. Then proliferation, scratch and Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…Previous studies have shown that baicalein could inhibit MMP-1 expression [ 27 ], and our study verified that bicycling and MMP-1 exhibit high binding energy through molecular docking. However, the downregulation of MMP‑1 expression inhibited the progression of colorectal cancer [ 28 ], it could thus be speculated that baicalein could slow down the progression of colorectal cancer by inhibiting MMP-1 expression. Kaempferol exhibits strong cytotoxic, anti-oxidant, anti-proliferative, and anti-apoptotic effects against HCT-116, HCT-15, SW480, and other CRC cells [ 29 ], and could also be used alone or combined with 5-FU to overcome CRC drug resistance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that baicalein could inhibit MMP-1 expression [ 27 ], and our study verified that bicycling and MMP-1 exhibit high binding energy through molecular docking. However, the downregulation of MMP‑1 expression inhibited the progression of colorectal cancer [ 28 ], it could thus be speculated that baicalein could slow down the progression of colorectal cancer by inhibiting MMP-1 expression. Kaempferol exhibits strong cytotoxic, anti-oxidant, anti-proliferative, and anti-apoptotic effects against HCT-116, HCT-15, SW480, and other CRC cells [ 29 ], and could also be used alone or combined with 5-FU to overcome CRC drug resistance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, CA 2 overexpression can improve the CRC cells’ sensitivity to chemotherapy drugs, which may be a potential biomarker for early CRC diagnosis [ 38 ]. Research shows that the expression of MMP-1 in colorectal cancer tissues is higher than that in normal colon tissues, and MMP-1 may influence the occurrence and development of colorectal cancer through EMT and Akt signaling pathways [ 28 ]. In conclusion, the targets of the XCHT active ingredients interact with the disease targets of CRC, giving full play to the unique advantages of multi-compounds and multi-targets of traditional Chinese medicine to prevent and treat CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase-1 (MMP-1), also known as collagenase-1, has been demonstrated to mediate the pathological progression of diverse cancers [ 72 , 73 , 74 ]. Wang et al demonstrated that MMP-1 knockdown suppressed the progression of CRC by inhibiting the PI3K/Akt/c-myc signaling pathway and EMT [ 75 ]. All these results indicate that ECM-related EMT and IL-17 signaling pathways are strongly associated with the poor prognosis of right-sided colon cancers.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the CXCL8 level in the tumor microenvironment can promote the development of bladder cancer, and promote the angiogenesis and proliferation of tumor cells [18]. MMP1 is a mesenchymal collagen in the extracellular matrix, which involved in tumor behavior, and can promote the occurrence and metastasis of colorectal cancer through endothelial-mesenchymal transition and the protein kinase B signaling pathway [19]. ALB has an antioxidant effect in the blood vessels of people suffering from benign paroxysmal positional vertigo (BPPV), and a decrease in the serum level of ALB is related to BPPV pathogenesis [20].…”
Section: Discussionmentioning
confidence: 99%